Reducing unacceptable missed doses: pharmacy assistant-supported medicine administration. (28th January 2015) - Baqir, Wasim; Jones, Kate; Horsley, William; Barrett, Scott; Fisher, David; Copeland, Richard; Campbell, David; Stephenson, Rosemary
Abstract: Objectives: The potential harm from omitted and delayed medicines for hospital inpatients was highlighted by the National Patient Safety Agency (NPSA). Despite evidence of omitted doses, few interventional studies have been reported on preventing the problem. This study aimed to assess the impact on omitted doses when medicine administration was supported by pharmacy assistants (PAs). Methods: PAs were trained to support nurses on medicine administration rounds. Using stratified random sampling, two intervention and control wards were selected. Three study groups were defined: (A) intervention group (PA-supported medicine administration); (B) intra-ward control group; and (C) inter-ward control group. Primary outcome measure was number of patients with unacceptable omitted doses (UODs) in group A versus C. Secondary outcome measures were patients with critical UOD (cUOD), as defined by the NPSA, in groups A, B and C and UODs in group B versus A and C. Data were collected over 2 weeks (December 2011 and February 2012). Key findings: Using aggregated data over 2 weeks, 778 patients were assessed; 308 were male (40%). The overall proportion of patients with ≥1 UOD was 12.4% ( n = 96). The proportion of patients with ≥1 UOD was 1.1% ( n = 2) in group A (intervention) and 18.5% ( n = 68) in group C (control). There were significantly fewer patients with cUOD in group A (1.1%; n = 2) compared with group C (7.4%; n = 27). Conclusion: PA-supported medication rounds can significantly reduce the rate of omitted doses. This study provides evidence for a potential solution to the problem of omitted doses for hospital inpatients.